2012
DOI: 10.1063/1.4764927
|View full text |Cite
|
Sign up to set email alerts
|

Optical characteristics of GaAs nanowire solar cells

Abstract: The reflectance, transmittance, and absorptance of GaAs nanowire (NW) arrays are calculated by solving Maxwell's equations using the finite element method. The model is compared with measurement results from well-ordered periodic GaAs NW arrays fabricated by dry etching. The model results are also compared with the reflectance measured from NWs grown by the Au-assisted vapor-liquid-solid method. The optimum NW diameter, periodicity (spacing between NWs), and length are determined to maximize absorptance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…Similar enhancements have been reported for Ge 101, GaP 102, 103, InP 103–106 and InAs nanowires 106. Hu et al 107, 108 found that a diameter of 180 nm and period (spacing between nanowires) of about 350 nm yielded the highest short‐circuit current in a GaAs‐on‐GaAs or GaAs‐on‐Si nanowire solar cell. Similar results have been obtained by other groups 105, 106, 109, 110.…”
Section: Optical Absorptionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar enhancements have been reported for Ge 101, GaP 102, 103, InP 103–106 and InAs nanowires 106. Hu et al 107, 108 found that a diameter of 180 nm and period (spacing between nanowires) of about 350 nm yielded the highest short‐circuit current in a GaAs‐on‐GaAs or GaAs‐on‐Si nanowire solar cell. Similar results have been obtained by other groups 105, 106, 109, 110.…”
Section: Optical Absorptionsupporting
confidence: 71%
“…Besides tuning the diameter and period of nanowire arrays, absorption and the resulting photocurrent density from a nanowire PV device can also be optimized by increasing the length of nanowires. Figure 2 shows the simulated contribution to the total photocurrent from the nanowires and the substrate in a GaAs nanowire PV device for a nanowire diameter of 180 nm and a period of 350 nm 108. As the nanowire length increases, the contribution from the nanowire to the total photocurrent increases, while the GaAs substrate contribution correspondingly decreases.…”
Section: Optical Absorptionmentioning
confidence: 99%
“…There is a need for fast, accurate modeling tools to enable rapid exploration and optimization of nanowire designs. Conventionally, finite element [4,[9][10][11] and finite difference methods [1,12,13] have been used in optical models of NWSC. While these techniques are highly accurate, they are computationally expensive, limiting their usefulness in a closed-loop global device optimization.…”
Section: Introductionmentioning
confidence: 99%
“…When we include a metal like Au into our nanowire system, we expect an increase in the reflection [15,28]. However, as presented above, the observed main optical effect of the Au particles is a 50% broadband absorption, even though the Au particles cover only <15% of the area in the plane of the nanowire array.…”
Section: Discussion and Outlookmentioning
confidence: 88%
“…Theoretical modeling has shown that the absorption of light in such arrays can be nearly as efficient as in a corresponding bulk cell [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%